Rieske Iron-Sulfur Isoforms in a Unicellular Cyanobacterium - Schettle, Sarah (My University, 2007)
Rieske iron-sulfur proteins (ISPs) are integrally involved in photosynthetic electron transport chains and thus closely linked to energy production and its regulation in cyanobacteria and plant chloroplasts. The cyanobacterium Synechocystis sp. PCC 6803 has three Rieske proteins, PetC1, PetC2, and PetC3, whose specific roles are not well understood. Here we describe two-dimensional (2D) gel electrophoresis and immunoblotting used to investigate the PetC1 Rieske protein in native Synechocystis and to confirm its absence in a mutant with an inactivated PetC1 gene. These studies revealed a “trail” of PetC1 Rieske protein spots migrating at the same molecular weight on 2D gels but at different isoelectric points. This “stuttering” phenomenon suggests covalent modifications that may reflect oxidative damage or modifications of the protein involved in biochemical signaling reactions.
Oshkosh Scholar, Volume 2, 2007, p. 81-89.
Keywords: Chloroplasts; Plants, Effect of light on.; Photosynthesis; Electron transport; Cyanobacteria